(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2026)
Vocabulary is one of the basic components of language learning, as it is necessary for achieving fluency in language skills. However, many students struggle with vocabulary learning challenges, which negatively impact their academic performance. The proposed study aims to identify the difficulties faced by English language students in learning vocabulary and to suggest strategies for improvement. This research is based on quantitative research methods using a questionnaire. The data were analyzed using SPSS. Participants were thirty English students at the English Department of Derna University- Al-Qubbah branch- (fifteen from the first year and fifteen from the third year). The questionnaire asked students what strategies they used to learn new English vocabulary. The results indicated that key difficulties reported include short-term memory issues, difficulty with long words, incorrect usage, and lack of practice. The study recommends incorporating visual aids, definitions, drawing, feedback, and group role-play.